Analysis of the spinal cord angle for severe cervical ossification of the posterior longitudinal ligament: comparison between anterior controllable antedisplacement and fusion (ACAF) and posterior laminectomy - Sun, Kaiqiang; Wang, Shunmin; Huan, Le; Sun, Jingchuan; Xu, Ximing; Sun, Xiaofei; Shi, Jiangang; Guo, Yongfei (European spine journal, 2020)
Objective To investigate the changes of spinal cord angle between anterior controllable antedisplacement and fusion (ACAF) and posterior laminectomy in treating severe ossification of the posterior longitudinal ligament (OPLL). Patients and methods Seventy-one patients with cervical OPLL were enrolled. Patients in this study were divided into group A and group P. Japanese Orthopaedic Association (JOA) score was utilized to evaluate the neurological function. Radiological assessments included the spinal cord angle, Cobb angle, and area of the spinal cord. Surgery-related complications were also recorded. Results At the final follow-up, patients in group A had better recovery of local and whole cord angle, and the area of the cord than those in group P (all p < 0.05). A strong correlation between the change of local cord angle and the recovery of the spinal cord area was observed ( r = − 0.867, p < 0.05). In addition, patients in group P had worse Cobb angle (9.15° ± 1.10°) than in group A (18.58° ± 0.73°) ( p < 0.05). The final mean JOA score and its improvement rate were better in the group A than in group P ( p < 0.05). During the follow-up, 15.15% patients in group P experienced surgery-related complications and 7.89% in group A. Conclusion This present study revealed that ACAF can achieve better recovery of the expansion of the spinal cord, spinal cord alignment, and Cobb angle, with better postoperative JOA score and less complications, compared with posterior laminectomy in treating severe cervical OPLL. Graphical abstract These slides can be retrieved under Electronic Supplementary Material.